Animal hide glue manufacturing plant - Chua, Philip; Sy, Paul.; Lip, Wee Ki. (Diliman, Quezon City College of Engineering, 1974)
Capacity: 2,200 lb/day -- Total fixed capital investment: P 12,542,551 -- Total product cost at max. production: P 2,191,739 -- Annual sales at max. production: P 4,201,848 -- Pay-out time: 3.84 years -- Max. annual rate of production: 660,000 lbs./yr. -- Break even point: 28.5% of max. production -- Percent return on fixed capital investment before taxes: 16.1%
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Bone products; Adhesives; Glue